Effect of Outsourcing Strategies on the Operational Performance of Small and Medium Scale Enterprises in Ghana - Johnson NSOWAH; Maxwell Agabu PHIRI (International Journal of Environmental, Sustainability, and Social Science, 2023)
The study examined the effect of outsourcing on the operational performance of small and medium enterprises (SMEs). Using questionnaires, a descriptive research design was employed with a sample size of 68 SMEs in Sunyani Municipality. The data analysis was based on a mean score and standard deviation using SPSS. The nature of outsourcing recorded in the study was the SMEs outsourcing some of their activities (mean score = 4.47, SD = 0.47), the practice affecting all areas of their operations (mean score = 4.24, SD = 0.47), and specifically internal operations (mean score = 4.17, SD = 0.55). The reasons SMEs in Sunyani practice outsourcing are to free up the company's resources to focus on its core competencies (mean score = 4.41, SD = 0.37), improve its competitive position (mean score = 4.26, SD = 0.41), avoid labour issues (mean score = 4.11, SD = 0.43), reduce cost (mean score = 3.82, SD = 0.52), reduce the risk associated with in-house production (mean score = 3.80, SD = 0.54), and increase efficiency (mean score = 3.75, SD = 0.60). The effects of outsourcing on operations and service delivery are reduced through superior provider performance, and the provider's lower cost structure (mean score = 4.21, SD = 0.43) and existing skills are commercially exploited (mean score = 4.18, SD = 0.47). Therefore, SMEs in Sunyani are encouraged to continue with their outsourcing practices. However, further study is recommended on the factors and challenges affecting outsourcing among Ghanaian companies.